β2 integrin mediates hantavirus-induced release of neutrophil extracellular traps - Raftery, Martin J; Lalwani, Pritesh; Krautkrӓmer, Ellen; Peters, Thorsten; Scharffetter-Kochanek, Karin; Krüger, Renate; Hofmann, Jörg; Seeger, Karl; Krüger, Detlev H; Schönrich, Günther (The Journal of experimental medicine, 2014)
Rodent-borne hantaviruses are emerging human pathogens that cause severe human disease. The underlying mechanisms are not well understood, as hantaviruses replicate in endothelial and epithelial cells without causing any cytopathic effect. We demonstrate that hantaviruses strongly stimulated neutrophils to release neutrophil extracellular traps (NETs). Hantavirus infection induced high systemic levels of circulating NETs in patients and this systemic NET overflow was accompanied by production of autoantibodies to nuclear antigens. Analysis of the responsible mechanism using neutrophils from β2 null mice identified β2 integrin receptors as a master switch for NET induction. Further experiments suggested that β2 integrin receptors such as complement receptor 3 (CR3) and 4 (CR4) may act as novel hantavirus entry receptors. Using adenoviruses, we confirmed that viral interaction with β2 integrin induced strong NET formation. Collectively, β2 integrin-mediated systemic NET overflow is a novel viral mechanism of immunopathology that may be responsible for characteristic aspects of hantavirus-associated disease such as kidney and lung damage.